PENGARUH LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK (Studi Kasus: Mahasiswi FEBI IAIN Langsa) - febi febi; Ismail Fahmi Arrauf Nst; Fahrizal Fahrizal; Fauziah Fauziah (JIM: Jurnal Ilmiah Mahasiswa, 2019)
The concept of halal for moslem comprises the whole aspect of good and cleand that can be consumed and used by human based on Islamic sharia. The moslem consumers can easily identify the product with “ Halal “ label on it. This study aims to determine whether there is an influence of the label of halal of students’ decision in purchasing the cosmetic product and to investigate how much the students’ atfention on halal label on cosmetic product. 102 students were the sample of this study which has selected by using simple random sampling. The data then were analyzed by using statistical test with simple regression test. The result showed that halal label influenced the student’s decision on purchasing the cosmetic product by 23,4%. The percentage of student’s attention on halal label on cosmetic product stood at 0,484% only. The rest percentage if 76,6% was influenced by other variable that was not mentioned in this model. In terms of micro economy, consumptive behavior affects on the Indonesian economy in islam, it is prohibited due to it can lead to be wasted moslems are guided to fulfill their needs based on syari’ah in order to achieve prosperous and happy lives both in the world and here after.